2015
DOI: 10.1148/radiol.15141488
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium Chelate Contrast Material in Pregnancy: Fetal Biodistribution in the Nonhuman Primate

Abstract: Purpose:To determine the extent to which gadolinium chelate is found in nonhuman primate fetal tissues and amniotic fluid at 19-45 hours after intravenous injection of a weight-appropriate maternal dose of the contrast agent gadoteridol. Materials and Methods:Gravid Japanese macaques (n = 14) were maintained as approved by the institutional animal care and utilization committee. In the 3rd trimester of pregnancy, the macaques were injected with gadoteridol (0.1 mmol per kilogram of maternal weight). Fetuses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 42 publications
3
38
0
1
Order By: Relevance
“…To determine the potential Gd 3+ fetal toxicity after maternal gadoteridol intravenous injection, Oh et al [209] obtained concentrations of the Gd chelate in nonhuman primate placenta, fetal tissues, and amniotic fluid. Compared to the maternal injected dose, the Gd complex concentrations in the fetal tissues and amniotic fluid were minimal, which may alleviate some concerns regarding MRI Gd chelate administration during pregnancy.…”
Section: Organismsmentioning
confidence: 99%
“…To determine the potential Gd 3+ fetal toxicity after maternal gadoteridol intravenous injection, Oh et al [209] obtained concentrations of the Gd chelate in nonhuman primate placenta, fetal tissues, and amniotic fluid. Compared to the maternal injected dose, the Gd complex concentrations in the fetal tissues and amniotic fluid were minimal, which may alleviate some concerns regarding MRI Gd chelate administration during pregnancy.…”
Section: Organismsmentioning
confidence: 99%
“…An extensive literature review could not identify any fetal effect following intrauterine exposure . Although gadolinium crosses the placenta into the fetal circulation, to be excreted by the fetal kidneys into the amniotic fluid, a recent study in a nonhuman primate model demonstrated that minimal amounts of gadolinium are found in fetal tissue and amniotic fluid, compared with the dose injected into the mother …”
Section: Introductionmentioning
confidence: 99%
“…33 Corroborating this theory, a study performed in gravid macaques showed the highest amniotic fluid concentration of GBCAs at 19-21 hours after maternal administration followed by a statistically significant decline at 45 hours. 34 In that study, the liver was the site of second greatest visceral GBCA accumulation (after the kidney), containing 0.0013% of the injected dose per gram of tissue at 45 hours postinjection. In contrast, only 0.00002% of injected GBCA dose was detectable within the fetal brain on a pergram basis at this same timepoint.…”
Section: Pregnancy and Lactationmentioning
confidence: 87%
“…Once within the fetal circulatory system, GBCAs undergo renal clearance and enter the amniotic fluid via excretion from the urinary bladder, after which fetal swallowing is thought to result in gastrointestinal reabsorption . Corroborating this theory, a study performed in gravid macaques showed the highest amniotic fluid concentration of GBCAs at 19–21 hours after maternal administration followed by a statistically significant decline at 45 hours . In that study, the liver was the site of second greatest visceral GBCA accumulation (after the kidney), containing 0.0013% of the injected dose per gram of tissue at 45 hours postinjection.…”
Section: Pregnancy and Lactationmentioning
confidence: 92%